2015
DOI: 10.1371/journal.pone.0116954
|View full text |Cite
|
Sign up to set email alerts
|

Color-Shape Associations Revealed with Implicit Association Tests

Abstract: Kandinsky proposed a correspondence theory that suggests associations between specific colors and shapes (i.e., circle-blue, square-red, triangle-yellow). Makin and Wuerger tested the theory using the Implicit Association Test (IAT) and did not find clear evidence for Kandinsky’s color-shape associations among British participants. In the present study, we first replicated the previous study among Japanese participants and found similar results to those of Makin and Wuerger, showing little support for Kandinsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 13 publications
7
60
0
Order By: Relevance
“…Kandinsky (1912/1994 , 1947 ), renowned abstract painter, proposed a correspondence theory between shapes and colors that state that circle, square, and triangle are associated with blue, red, and yellow, respectively. Kandinsky’s correspondence theory became influential in art and design theory ever since it was proposed, but, researchers and artists showed different patterns of color-shape associations ( Lupton and Miller, 1993 ; Jacobsen, 2002 ; Jacobsen and Wolsdorff, 2007 ; Dumitrescu, 2011 ; Kharkhurin, 2012 ; Albertazzi et al, 2013 ; Chen et al, 2015a , b ). For example, Jacobsen (2002) used a modified version of Kandinsky’s questionnaire and found that German participants tended to associate red with triangle, blue with square, and yellow with circle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kandinsky (1912/1994 , 1947 ), renowned abstract painter, proposed a correspondence theory between shapes and colors that state that circle, square, and triangle are associated with blue, red, and yellow, respectively. Kandinsky’s correspondence theory became influential in art and design theory ever since it was proposed, but, researchers and artists showed different patterns of color-shape associations ( Lupton and Miller, 1993 ; Jacobsen, 2002 ; Jacobsen and Wolsdorff, 2007 ; Dumitrescu, 2011 ; Kharkhurin, 2012 ; Albertazzi et al, 2013 ; Chen et al, 2015a , b ). For example, Jacobsen (2002) used a modified version of Kandinsky’s questionnaire and found that German participants tended to associate red with triangle, blue with square, and yellow with circle.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed little support for Kandinsky’s correspondence theory, except only a marginal effect for one pair of combinations (square-red and triangle-yellow associations) among the three combinations they tested (the other two combinations: circle-blue and square-red, circle-blue and triangle-yellow associations). Then, Chen et al (2015b) initially verified whether those Japanese color-shape associations (e.g., circle-red, triangle-yellow, square-blue) could be measured by the IAT. They found that RTs were significantly faster when the visual stimuli of circle-red, triangle-yellow, and square-blue combinations were mapped onto the same response key, rather than different key combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Kandinsky's proposition was also tested by other studies using direct matching [5][6][7] and implicit tests such as a priming and color/form recognition test 8 and an implicit association test (IAT). 9 Although the triangle-yellow association was supported in the majority of the studies, the red-square and blue-circle associations were not supported in any of them.…”
Section: Introductionmentioning
confidence: 87%
“…The RGB hex codes were #0000FF for the blue colour, and #FF0000 for the red colour. A variety of shapes were selected to avoid possible confounds a single colour-shape combination might have, as there is some evidence that certain colour-shape associations exist, and that these associations can influence speed and accuracy results on the IAT (Chen, Tanaka, & Watanabe, 2015;cf. Makin & Wuerger, 2013).…”
Section: Methodsmentioning
confidence: 99%